Increasing Patient Acceptance and Adherence Toward Insulin: Highlights from a CME symposium held at the Cardiometabolic Health Congress (CMHC) Sheraton Boston Hotel, Boston, MA 23 October 2015. (30th September 2016) - Riddle, Matthew; Peters, Anne; Funnell, Martha
ABSTRACT: Because of the progressive nature of type 2 diabetes mellitus (T2DM), the majority of patients will need insulin to achieve and maintain glycemic control. By maintaining glycemic control, patients will avoid acute osmotic symptoms of hyperglycemia, instability in plasma glucose (PG) over time, and prevent or delay the development of diabetes complications without adversely affecting quality of life. Despite recommendations for initiating insulin therapy, both patient and health system barriers stand in the way. To develop confidence in individualizing patient therapy and maximize outcomes for patients with T2DM, healthcare practitioners (HCPs) were updated on recommendations and clinical evidence supporting when to initiate insulin therapy, strategies for overcoming provider and patient barriers for initiating insulin therapy, and the safety and efficacy of current and emerging insulin therapy and delivery technology for patients with T2DM.